Prolonged stabilization of progressive squamous cell cancer of the cervix with interferon-α and 13-cis-retinoic acid: Report of two cases and review of the literature - Surintip Piamsomboon (2018)
Recurrent and metastatic cervical carcinoma has very poor prognosis, mainly because there is no effective systemic therapy which would increase the duration of survival. Biologic agents have recently been found to have activity in cervical carcinoma. The combination of interferon (IFN)-α and 13-cis-retinoic acid has additive and synergistic antitumor activity. Both have antiviral, immunoregulatory and antiangiogenic properties, and are known to modulate malignant cell differentiation and proliferation. We report two patients with recurrent squamous cell carcinoma (SCC) of the cervix who had small-volume progressive metastatic disease, and were treated with a combination of IFN-α and 13-cis-retinoic acid. The first patient had pelvic lymph node metastases and the other had lung metastases. The previously progressive diseases remained stable for a prolonged period of time, 3 and 4 years, with a good quality of life. These cases suggest the possibility of using IFN-α and 13-cis-retinoic acid as a treatment for small-volume residual disease or as postinduction therapy in patients at high risk for disease recurrence.